FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PENUSUPAN KABUPATEN TEGAL - Eko Nuryanto; Endo Dardjito; Erna Kusuma Wati (Kesmas Indonesia, 2012)
ABSTRACT Anemia is one of the major nutritional problem in Indonesia. Anemia is a condition in which the levels of hemoglobin (Hb) in the blood less than normal, normal levels for pregnant women was 11.0 g%. This study aims to determine the factors that influence the incidence of anemia in pregnant women in Penusupan health center Tegal District. This type of research is explanatory research with cross sectional approach. The sample in this study were 65 respondents. Results showed the majority of pregnant women (61.5%) had anemia. The results of bivariate analysis showed that factors affecting the incidence of anemia among pregnant women is gestational age (p = 0.007), and iron consumption rate (0.000), while the variables that influence the variable level of knowledge to the value of p <0.029 (p <0.05) and the level of iron consumption with the p-value = 0.000 (p <0.05). Advice for pregnant women should alter the pattern of consumption of tea or coffee drinks that can inhibit the absorption of iron by replacing materials consumed a drink containing vitamin C so it can accelerate the process of iron absorption. Keyword : anemia, consumption of iron, pregnant women Kesmasindo Volume 5(1) Januari 2012, hlm. 23-32